Islamic Law and Ethics: The Role and Obligations of Marriage for Individuals with Intellectual Disabilities - Sabri, Fahruddin Ali (Nursyam Centre, 2024)
This article examines Islamic law and ethics used to analyze the position and ethics of persons with intellectual disabilities in marriage. They have the same right to marry without discrimination or stigma. Literary and descriptive methods were used in this study, as well as document comparison. The study found that Islamic scholars of various schools expressed their opinions about the marriages of people with intellectual disabilities and their legal responsibilities. Although the majority of madhhabs recognize that their marriages are valid, there are questions about their responsibilities after the marriage. This issue is addressed in several edicts of scholars; Some of them allow marriage if there is sexual attraction. However, the question of how they can take responsibility and consent in the context of sexuality is still the subject of discussion. To determine whether people with intellectual disabilities can fulfill their marital obligations, the concept of responsibility, both etymological and terminological, is discussed. Studies show that a person's ability to take responsibility is affected by their level of disability. This perspective discusses the impact of Islamic law and the daily lives of people with intellectual disabilities, such as the possibility of guardianship or representation in decisions about marriage and sexuality. According to this study, the personal responsibilities and rights of people with intellectual disabilities should be carefully considered.